Human-computer interaction in game development with Python : design and develop a game interface using HCI technologies and techniques - George, Joseph Thachil; George, Meghna Joseph (Apress, 2022)
Deepen your understanding of human-computer interaction (HCI) in game development and learn how to develop video games that grab players and don't let them go. This book explores HCI design in computer games to maximize collaborative and interactive functions. You'll first gain a basic introduction to fundamental concepts and practices of HCI before diving into the fundamental concepts of game interface design and technology. You'll learn how to design a gaming interface through practical examples using Python. This is followed by a brief look at how HCI can offer immersive gaming experiences for players and a review of key elements such as interface, usability, user-centered design, and user interface in terms of efficacy. You will also learn how to implement usability aspects in gaming interfaces with examples using Python. Additionally, the book discusses major challenges that game publishers and developers face, and how they can be resolved using HCI techniques. The question of playability is reviewed throughout the game production process. After working through this book's practical examples, you'll have the knowledge required to begin developing compelling, can't-put-the-controller down games of your own. What You'll Learn Master HCI tools and methodologies Understand the concept of HCI strategies in the game development cycle Develop a game in Python using the HCI approach Utilize gamification techniques in Human-Computer Interaction Grasp concepts of usability, user experience and user-centered design processes and their application Who This Book Is For Programmers, engineers, and students interested in creating and implementing computer games using HCI technologies. Prior experience with game development is recommended.